Nanomedicine-Mediated Therapies to Target Breast Cancer Stem Cells - He, Lili; Gu, Jian; Lim, Lee Y.; Yuan, Zhi-xiang; Mo, Jingxin (Frontiers in Pharmacology, 2016)
Accumulating evidences have suggested the existence of breast cancer stem cells (BCSCs), which possess the potential of both self-renewal and differentiation. The origin of BCSCs might have relationship to the development of normal mammary stem cells. BCSCs are believed to play a key role in the initiation, recurrence and chemo- and/or radiotherapy resistances of breast cancer. Therefore, elimination of BCSCs is crucial for breast cancer therapy. However, conventional chemo and radiation therapies cannot eradicate BCSCs effectively. Fortunately, nanotechnology holds great potential for specific and efficient anti-BCSCs treatment. “Smart” nanocarriers can distinguish BCSCs from the other breast cancer cells and selectively deliver therapeutic agents to the BCSCs. Emerging findings suggest that BCSCs in breast cancer could be successfully inhibited and even eradicated by functionalized nanomedicines. In this review, we focus on origin of BCSCs, strategies used to target BCSCs, and summarize the nanotechnology-based delivery systems that have been applied for eliminating BCSCs in breast cancer.